Lottery sales and per-capita GDP : an Inverted U relationship - Kaiseler, Maria João (2008)
The main purpose of this study is to test the hypothesis that the relationship between per-capita sales and per-capita GDP is given by an inverted U. The paper considers that lottery sales increase together with increases in GDP up to a point where a country has reached a level at which the GDP is high enough and lottery sales become an inferior good and as a result, start to decrease. As there are other determinants of the expenditure on lottery products, the paper introduces into the regression analysis other explanatory factors as control variables. The paper uses a cross-country regression, using 2004 data for 80 countries. The results confirm the hypothesis, in addition to yielding other interesting findings: countries with higher levels of education sell fewer lottery products; lottery sales increase together with increases in the male to female ratio.